2016
DOI: 10.1002/pat.3910
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir–Schaefer films of fibronectin as designed biointerfaces for culturing stem cells

Abstract: Glycoproteins adsorbing on an implant upon contact with body fluids can affect the biological response in vitro and in vivo, depending on the type and conformation of the adsorbed biomacromolecules. However, this process is poorly characterized and so far not controllable. Here, protein monolayers of high molecular cohesion with defined density are transferred onto polymeric substrates by the Langmuir–Schaefer (LS) technique and were compared with solution deposition (SO) method. It is hypothesized that on pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On a Langmuir trough, monolayers with a precisely defined degree of degradation can be prepared conveniently and rapidly. After Langmuir–Schäfer transfer to solid substrates, the bioresponse to materials prepared on a Langmuir trough can be investigated, for example, in cell culture . Another aspect related to the bioresponse to a biodegradable material is the nature of the fragments generated during the degradation process.…”
Section: Further Challenges and Perspectivesmentioning
confidence: 99%
“…On a Langmuir trough, monolayers with a precisely defined degree of degradation can be prepared conveniently and rapidly. After Langmuir–Schäfer transfer to solid substrates, the bioresponse to materials prepared on a Langmuir trough can be investigated, for example, in cell culture . Another aspect related to the bioresponse to a biodegradable material is the nature of the fragments generated during the degradation process.…”
Section: Further Challenges and Perspectivesmentioning
confidence: 99%
“…Both proteins exhibit a change in the specific area depending on the pH value. FN monolayers of high molecular cohesion with defined surface density have been transferred onto polydimethylsiloxane (PDMS) substrates by the LS-method to improve stem cell adhesion behaviour [139]. LS layers are shown to be uniform and homogeneous as indicated by AFM and immunofluorescence images, whereas layers prepared by solution deposition method are rather heterogeneous with the appearance of resembling protein aggregates.…”
Section: Other Proteinsmentioning
confidence: 99%
“…For example, Fernandes et al demonstrated the penetration of nano-penicillin G spheres within Langmuir monolayers formed by L-α-phosphatidylethanolamine, the principal phospholipid extracted from E. coli [16]. However, despite remarkable examples of cell culture over Langmuir, Langmuir-Blodgett and Langmuir-Sch€ afer layers [17,18], to the best of our knowledge, few studies have been developed using monomolecular Langmuir-Blodgett films acting as biomimetic drug reservoir and delivery systems [11,12,19]. Higuchi et al demonstrated that fibroblast L929 cells cultured on collagen adhered and spread better on synthetic polymeric films prepared by the LB method than on films obtained by the casting method [20].…”
Section: Introductionmentioning
confidence: 99%
“…Also, human interferon-β was produced by inoculation of fibroblast cells cultured on polymeric films obtained by the Langmuir-Blodgett technique [21]. Recently, Bhuvanesh et al reported the building of artificial biomimetic structures, where the cell stem adhesion can be directed by the surface areal density of collagen type-4 in Langmuir films [17]. Similarly, hippocampal pyramidal neurons were cultured onto LB films of insulin with different surface packing density, showing that the neuron polarization through the activation of the Insulin-like Growth Factor-1 receptor can be selectively modulated by the lateral packing of insulin, organized as a monomolecular surface for cell growth [22].…”
Section: Introductionmentioning
confidence: 99%